2010
DOI: 10.1007/s10555-010-9207-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation markers in colorectal cancer

Abstract: Colorectal cancer (CRC) arises as a consequence of the accumulation of genetic and epigenetic alterations in colonic epithelial cells during neoplastic transformation. Epigenetic modifications, particularly DNA methylation in selected gene promoters, are recognized as common molecular alterations in human tumors. Substantial efforts have been made to determine the cause and role of aberrant DNA methylation ("epigenomic instability") in colon carcinogenesis. In the colon, aberrant DNA methylation arises in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
208
0
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(223 citation statements)
references
References 189 publications
(316 reference statements)
7
208
0
8
Order By: Relevance
“…DFNA5 methylation has been observed in DNA from the peripheral blood (PB) of CRC patients at a high frequency (48% or 12/25) relative to healthy controls (only 12% or 3/25). Moreover, the methylation of DFNA5 in PB samples from CRC patients was significantly correlated with lymph node metastasis and distant metastasis (P = 0.027) [5] , which suggests that DFNA5 could potentially be an independent prognostic serum biomarker for CRC patients. It is clear, however, that further validation in large-scale prospective trials is necessary before these biomarkers are ready for use in the clinic [26] .…”
Section: Mirna Biomarkers Mirna and Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…DFNA5 methylation has been observed in DNA from the peripheral blood (PB) of CRC patients at a high frequency (48% or 12/25) relative to healthy controls (only 12% or 3/25). Moreover, the methylation of DFNA5 in PB samples from CRC patients was significantly correlated with lymph node metastasis and distant metastasis (P = 0.027) [5] , which suggests that DFNA5 could potentially be an independent prognostic serum biomarker for CRC patients. It is clear, however, that further validation in large-scale prospective trials is necessary before these biomarkers are ready for use in the clinic [26] .…”
Section: Mirna Biomarkers Mirna and Cancermentioning
confidence: 93%
“…Epigenetic changes in colorectal tumor tissues and CRC cell lines have been widely reported, and a substantial amount of information has been accumulated [4,5] . These alterations include aberrant DNA methylation of promoter CpG islands, changes in microRNA (miRNA) expression profiles and various histone modifications.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation can be detected in tumor-derived DNA found in the bloodstream or in samples of body fluids obtained from cancer patients. If optimal sensitivity and specificity is gained through the identification of markers that show the highest differences in methylation between the cancer and the background, testing for methylated DNA in blood or stool samples may have great potential as a new screening marker for CRC as well as a tool for disease monitoring in colon cancer patients [70].…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
“…Early detection of cancer, mainly at the onset of the disease, is a major goal of cancer research. The changes present in precancerous lesions [6] and some cancers [7] revealed that DNA methylation alterations play a key role in the early steps of human carcinogenesis. It has been a few decades now since Riggs, Holliday and Pugh proposed that DNA methylation was part of a system for controlling gene expression, and play an essential role in genome regulation, development and disease in mammalian cells [8,9].…”
Section: Introductionmentioning
confidence: 99%